Wireless Design And Optimization For Telkom University Landmark Tower (Tult) Floor 1 To 3 In 5ghz Frequency Based On Capacity And Workload Using The Ppdioo Method - Al Gilbran, Ksatria Vege; Hediyanto , Umar Yunan Septo; Fathinuddin, Muhammad (eProceedings of Engineering, 2024)
Abstract - Wireless Local Area Network (WLAN) is a type of network that uses wireless technology to connect devices sothey can connect to the internet. Wireless LAN network isalready a standard facility in various public places, especiallycampuses. WLAN is used to connect to the internet because ithas high bandwidth, low delays, and minimizes powerconsumption. Telkom University Landmark Tower (TULT) building is abuilding that was built at a height of 19 floors and is a smartbuilding-based lecture building that supports the concept of gogreen. TULT building applies the 5GHz band frequency toprovide internet access to people who use it. However, theperformance of the WLAN is not satisfactory, with several problems such as capacity or workload for daily use of useraccess activity. To overcome these problems, it is necessary to optimize thedesign and performance of WLANs operating in the TULTBuilding. The author focused on the research on the 1st to 3rdfloors of the TULT Building. The method that can be done is touse the Plan, Prepare, Design, Implement, Operate, andOptimize (PPDIOO) method. By using the PPDIOO method inoptimizing the 5GHz WLAN in the TULT Building, problems that impact network performance can be identified andresolved. With a focus on studying the capacity or workload to optimize 5GHz WLAN in the TULT Building floors 1 to 3. Keywords — 5ghz Wi-Fi, Telkom University LandmarkTower, Network Performance, Network Coverage, Quality Of Service (Qos), Network Infrastructure